1943
DOI: 10.1104/pp.18.4.588
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of the Velocity of Water Absorption in Individual Root Hairs by a Microtechnique

Abstract: POPESCO (11) credits the first observations on the absorption of solutes by roots to the work of MARCELLUS MALPIGHI in the seventeenth celntury. POPESCO writes that, in his work entitled Anatomne Plantarnin which appeared in 1675, MALPIGHI maintained that nutritive substances were absorbed by the roots at the level of the region of the root hairs. Since not all plants bear root hairs, MALPIGHI stated further that the entire epiderlial surface funetioned in absorption when root hairs were absent.According to PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1949
1949
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…As early as the seventeenth century, researchers began to realize that plants absorbed water rather than soil and that nutrient substances were absorbed by the roots at the level of the root hairs [ 15 , 16 , 17 ]. Typical root hairs have a cylindrical, straight form with a dome-shaped tip, that often form a right angle with the main root surface.…”
Section: Root Anatomy and Morphologymentioning
confidence: 99%
“…As early as the seventeenth century, researchers began to realize that plants absorbed water rather than soil and that nutrient substances were absorbed by the roots at the level of the root hairs [ 15 , 16 , 17 ]. Typical root hairs have a cylindrical, straight form with a dome-shaped tip, that often form a right angle with the main root surface.…”
Section: Root Anatomy and Morphologymentioning
confidence: 99%
“…Brooks & Brooks (13) cite other values and the existence of a considerable range of values is to be expected since permeability to water may vary from cell to cell and from tissue to tissue. Rosene (97) concluded that different parts of a given cell may vary in permeability to water as she found different rates of water intake through different parts of the same root cell. Perme ability varies with time and is involved in endogeneous rhythms manifested by plants [BUnning (32)].…”
Section: Permeability Of Cell Membranes To Watermentioning
confidence: 99%
“…In rice, Lan et al (2010) reported that the high-affinity K + transporter gene (OsHKT2;4), which is expressed in root hairs and vascular parenchyma cells, can function as a Ca 2+ -permeable cation channel. Importance of the root hairs in the water absorption was confirmed by the micropotometry experiment, a technique to measure water uptake directly using glass capillaries (Rosene 1943, Rosene andWalthall 1949).…”
Section: Introductionmentioning
confidence: 99%